Paradigma baru pendidikan IPS untuk meningkatkan SDM - Muhapi; Sugeng Aryo; ED Ismuttanti; Yayan Sudrajat (Lancar Media Komunikasi, 2023)
Quality education is strongly influenced by several factors, including teachers. In order to transfer his knowledge, a student must be able to acquire social skills and develop the application of democracy in his own life practice as an interaction with the community environment. Social studies education learning patterns should have been changed, both as teachers and students. Teachers as the vanguard have broad opportunities to open up carawala and treasures of mastery of approaches and methods for transforming social studies learning. Changing a new paradigm in social studies teaching is urgently needed nowadays, which aims to build good citizens. Students who receive social studies education can change their minds, that learning social studies can make these students ready to enter society under any circumstances. Through social studies education, it is hoped that civilized human resources (HR) will be formed, namely human resources who are educated (knowledgeable and skilled) and cultured (with strong character).